Guidelines for Adaptation of Ecotourism Logistics Businesses in Phra Nakhon Sri Ayutthaya Historical Park during Crisis - Dokmai, Ammara (Rajapark Journal, 2024)
The objectives of this research were 1) to examine the operations of ecotourism logistics businesses (ELB) in Phra Nakhon Sri Ayutthaya Historical Park, 2) to examine the factors of guidelines for adaptation of ELB, and 3) to develop a structural equation model of guidelines for adaptation of ELB. The sampling group consisted of ELB in Phra Nakhon Sri Ayutthaya Historical Park. The size of the sampling group was determined through cluster sampling and systematic random sampling methods. The qualitative research tool was an in-depth interview for analysis and a summary of guidelines for the adaptation of ELB to each factor. The quantitative research tool was a survey, and the data were analyzed using SPSS and AMOS. The research results were as follows: 1) The operations with the highest score were as follows: 1.1) tourism training businesses in partnership with governmental sectors; 1.2) public health safety standards certification through public health organizations; 1.3) public health safety standards participation for recognition; 1.4) promoting local authorities for innovation; 1.5) public health safety tools to support tourism; 1.6) Information Technology as a communication channel; 1.7) Information Technology for sales promotion; 1.8) Information Technology management to improve tourism; 1.9) publicity through social media. 2) There were 4 research factors as follows: 2.1) partnership ( = 4.15); 2.2 certification ( = 4.15); 2.3 innovation ( = 4.13); 2.4 Information Technology ( = 4.10); and 3) The analysis of structural equation modeling met the criteria. It was consistent with the empirical data (Chi-square value (χ2) of NN, degree of freedom (df) of NN, p-value of 0.128, relative chi-square χ2/df of 1.119, goodness of fit (GFI) of 0.962 and root mean square residual (RMR) of 0.015.